Kongo Graphic Writing and Other Narratives of the Sign - Martinez-Ruiz, Barbaro (Book collections on Project MUSE., 2013)
Written symbols, religious objects, oral traditions, and body language have long been integrated into the Kongo system of graphic writing of the Bakongo people in Central Africa as well as their Cuban descendants. This book provides a significant overview of the social, religious, and historical contexts in which the Kongo kingdom developed and spread to the Caribbean.